Building state capability: evidence, analysis, action - Andrews, Matt; Pritchett, Lant; Woolcock, Michael (United Kingdom Oxford University Press, 2017)
Governments play a major role in the development process, and constantly introduce reforms and policies to achieve developmental objectives. Many of these interventions have limited impact, however; schools get built but children don't learn, IT systems are introduced but not used, plans are written but not implemented. These achievement deficiencies reveal gaps in capabilities, and weaknesses in the process of building state capability. 00This book addresses these weaknesses and gaps. It starts by providing evidence of the capability shortfalls that currently exist in many countries, showing that many governments lack basic capacities even after decades of reforms and capacity building efforts. The book then analyses this evidence, identifying capability traps that hold many governments back - particularly related to isomorphic mimicry (where governments copy best practice solutions from other countries that make them look more capable even if they are not more capable) and premature load bearing (where governments adopt new mechanisms that they cannot actually make work, given weak extant capacities). The book then describes a process that governments can use to escape these capability traps.
Keywords: Political science; Economic policy